Journey of the pharaohs : a novel from the NUMA files - Cussler, Clive; Brown, Graham, 1969- (Cussler, Clive. NUMA files., 2020)
"Kurt Austin and the NUMA crew race to identify a link between an ancient Egyptian treasure, a 1927 daredevil aviators disappearance and the sinking of a modern fishing trawler to prevent a scheme by a cutthroat arms dealer."--